PENGARUH KERAGAMAN GENDER PADA DEWAN KOMISARIS, DEWAN DIREKSI, DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA - Naufal Afif Fitroni; Yie Ke Feliana (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2022)
The aim of this study is to identify the influence of gender diversity in the board of commissioners, board of directors, and audit committee for earnings management. This study in a quantitative tested with multiple linear regression. Gender diversity in this study was calculated using the proportion of female gender on each board. The object of this research is all companies listed in the Indonesia Stock Exchange (IDX), except for the financial sector for the period 2017-2019. The sample used in 1136 firms. The results of this study indicate that gender diversity on the board of directors has a positive effect on earnings management, while gender diversity on the board of commissioners and audit committee has no significant impact on earnings management. The conclusion obtained is that the presence of female gender on the board of directors will affect the earnings management, while on the board of commissioners and audit committee both male and female gender has an equal chance to do the earnings management.